2021
DOI: 10.1155/2021/6951578
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Total Knee Arthroplasty in the Treatment of Knee Osteoarthritis and Its Effect on Postoperative Pain and Quality of Life of Patients

Abstract: Objective. To explore the safety of total knee arthroplasty (TKA) in the treatment of knee osteoarthritis (KOA) and its impact on patients’ postoperative pain and quality of life. Methods. A total of 60 KOA patients admitted to our hospital from January 2019 to January 2020 were selected as the research objects. The knee joint scores (HSS) before and after TKA were compared, and the patients’ quality of life was evaluated using the Osteoarthritis Index of Western Ontario and McMaster University (WOMAC). At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Knee osteoarthritis (KOA) is a chronic joint disease. As the disease progresses patients often develop knee pain, stiffness, and deformity, limiting the patient's activities 1 . Total knee arthroplasty (TKA) has long been considered the definitive treatment for KOA, and successful TKA can reduce joint pain and restore function.…”
Section: Introductionmentioning
confidence: 99%
“…Knee osteoarthritis (KOA) is a chronic joint disease. As the disease progresses patients often develop knee pain, stiffness, and deformity, limiting the patient's activities 1 . Total knee arthroplasty (TKA) has long been considered the definitive treatment for KOA, and successful TKA can reduce joint pain and restore function.…”
Section: Introductionmentioning
confidence: 99%
“…These factors can contribute to the development of complications such as postoperative pain, motor dysfunction, bone fracture and postoperative infection, resulting in a negative impact on the patient's recovery and rehabilitation after surgery, particularly the lower limbs, directly influencing the patient's overall prognosis 29 . The treatment objective should focus on reducing pain and enhancing knee joint function to enhance patients' quality of life 30–34 . Therefore, the ERAS programs are gaining popularity due to their efficacy in reducing perioperative complications and expediting recovery 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that QoL advanced over time, consistent with other studies that have found that QoL at 3 months after TKA was better compared to that before TKA and that people resumed the vast majority of their daily activities at 12 months after TKA [ 9 , 26 ]. For a patient to undergo TKA, it must be perceived as high value in improving knee functions and relieving pain, and postoperative high intensity exercise and remote rehabilitation may be helpful in reducing joint stiffness [ 27 , 28 ]. Therefore, the physiological QoL can be improved accordingly during postoperative time.…”
Section: Discussionmentioning
confidence: 99%